Introduction to Statistical Data Analysis for the Life Sciences - Ekstrøm, Claus Thorn, Sørensen, Helle (CRC Press, Taylor & Francis, 2015)
Description of Samples and Populations Data types Visualizing categorical dataVisualizing quantitative data Statistical summaries What is a probability? R Linear Regression Fitting a regression line When is linear regression appropriate? The correlation coefficient Perspective R Comparison of Groups Graphical and simple numerical comparison Between-group variation and within-group variation Populations, samples, and expected values Least squares estimation and residuals Paired and unpaired samples Perspective R The Normal Distribution Properties One sample Are the data (approximately) normally.